Tuberculosis treatment outcomes and factors associated with each of them in a cohort followed up between 2010 and 2014 - Cardoso, M. A. (2017)
Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Programa de Pós-graduação em Pesquisa Clínica em Doenças Infecciosas. Rio de Janeiro, RJ, Brasil.